Perancangan Sistem Manajemen Arsip Berbentuk Digital Pada Jurusan Teknik Komputer Dan Informatika Politeknik Negeri Medan - GA Hutagalung; Isni Khairina; Rizki Syahputra (Ikatan Ahli Informatika Indonesia, 2021)
At the Department of Computer Engineering and Informatics at the Politeknik Negeri Medan, there is no digital technology-based system in handling archives, such as handling incoming letters, outgoing letters, assignments, etc. As an effort to increase the digitization of all forms of existing processes in the academic system in the Department of Computer and Informatics Engineering, digital archive management is needed. With a system that is able to manage archives in digital form, it can help the Department of Computer Engineering and Informatics in improving the quality and quality of study programs and departments to produce better accreditation of Study Programs for the future and become a major that is digitized in its academic system.